Parental Criticism and Emerging Adult Identity Confusion: The Moderating Role of Self-Compassion - Kröger , Anni; Hölling , Marc; Perchec , Feray (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to examine the relationship between parental criticism and identity confusion in emerging adults and to determine whether self-compassion moderates this relationship.Methods and Materials: A descriptive correlational design was employed with a sample of 422 emerging adults (aged 18–29) residing in Germany. Participants were recruited online and completed validated self-report questionnaires assessing parental criticism, self-compassion, and identity confusion. The sample size was determined according to the Morgan and Krejcie table to ensure adequate statistical power. Data analysis was conducted using SPSS-27 and AMOS-21. Descriptive statistics and Pearson’s correlation coefficients were computed to explore bivariate relationships among variables. Structural equation modeling (SEM) was performed to test the hypothesized model and to examine direct, indirect, and total effects, as well as the moderating role of self-compassion. Model fit was evaluated using multiple indices, including χ²/df, GFI, AGFI, CFI, TLI, and RMSEA.Findings: Results indicated a significant positive correlation between parental criticism and identity confusion (r = .52, p < .001) and a significant negative correlation between self-compassion and identity confusion (r = –.47, p < .001). SEM revealed that parental criticism directly predicted higher identity confusion (β = .49, p < .001), while self-compassion directly predicted lower identity confusion (β = –.38, p < .001). Parental criticism negatively predicted self-compassion (β = –.41, p < .001), and an indirect effect of parental criticism on identity confusion through reduced self-compassion was also significant (β = –.16, p < .001). The structural model demonstrated excellent fit (χ²/df = 2.01, CFI = .97, TLI = .96, RMSEA = .049).Conclusion: Parental criticism significantly contributes to identity confusion in emerging adults; however, self-compassion acts as a protective factor by buffering this adverse effect. Enhancing self-compassion may be an effective strategy to support identity development among individuals with critical parental backgrounds.